The impact of national context on future care planning for Korean parents in Korea and in New Zealand caring for their children living with disabilities: A cross-national study. (November 2021) - Choi, Clara; O'Brien, Mike
An increasing concern of families caring for children living with disabilities is related to planning for their future care. This qualitative study explores how the country contexts shape the plans for future care provision of Korean parents in New Zealand and Korea. Data were collected using semi-structured interviews with parents ( n  = 18) and professionals ( n  = 18). The study revealed that there are differences and similarities regarding the social reality of future care planning among Koreans in different national contexts. Recommendations are made In support of future care planning process taking its place as a conventional phase of care provision for people living with disabilities.